PERANCANGAN PEMASANGAN POMPA AIR BERSUMBER LISTRIK TENAGA MATAHARI DI PERSAWAHAN DESA SIRAISAN : Perancangan Pemasangan Pompa Air Bersumber Listrik Tenaga Matahari Di Persawahan Desa Siraisan - hasibuan, fardin (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2023)
Rice is a basic need in Indonesia. Siraisan Village, Ulu Barumun Sub-District, North Sumatra Province, is an area where most of the people are rice farmers. The success of rice planting need water to watering the rice field area, the contours of the hilly area become an obstacle in the water supply for the rice field area. The power grid that is not yet available in the rice field area, resulting in artificial irrigation is difficult to do, for that a special power plant is needed, the power plant used is a Solar Power Panel (PV), a pump can be installed to pump water from the river to irrigation the rice field area. The distance from river to rice field area about 315 meters and a height 3 meters from the normal river lip, results head loss 4.8 m , with a pipe diameter 4 inches. The coverage area of the rice field to be watered is 3 ha with a pump discharge of 600 liters / seconds, head 9 meters, power 3000 watts, AC one phase. The solar power plant is installed on 16 solar cell modules and investment cost Rp 131.996.483,00